A review on chemical constituents and biological activities of the genus beilschmiedia (Lauraceae) - Wan Salleh, Wan Mohd. Nuzul Hakimi (University of Benin, 2015)
The current review is aimed to deliver some updates on the ethnobotany, phytochemistry and biological activities of Beilschmiedia species in order to throw more light on their therapeutic potentials and future research priorities. Phytochemical studies on Beilschmiedia genus yielded essential oils, endiandric acid derivatives, amides/alkaloids, lignans/neoligans, flavonoids and miscellaneous compounds, while bioactivity studies revealed that the extracts and compounds displayed a broad spectrum of biological activities. Only 24 species of the genus Beilschmiedia have been studied phytochemically thus far. Therefore, there is a need to ascertain the pharmacological properties of the plant extracts and new compounds from this genus. More studies on the standardization and pharmacology of Beilschmiedia extracts need to be conducted to ascertain new pharmacological properties and their biochemical and physiological mechanisms. Furthermore, detailed preclinical toxicity, bioavailability, pharmacokinetics and pharmacodynamics of extracts of the species and their isolated compounds require additional investigation in order to verify their safety and determine their suitability as sources of some current medicines. © Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, Benin City, 300001 Nigeria. All rights reserved.